2023
DOI: 10.3389/ffgc.2023.1107417
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fire hazard in Southwestern Amazon

Abstract: Fires are among the main drivers of forest degradation in Amazonia, causing multiple socioeconomic and environmental damages. Although human-ignited sources account for most of the fire events in Amazonia, extended droughts may magnify their occurrence and propagation. The southwestern Amazonia, a transnational region shared by Brazil, Peru, and Bolivia and known as the MAP region, has been articulating coordinated actions to prevent disasters, including fire, to reduce their negative impacts. Therefore, to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…The fire foci found in Rio Branco were concentrated in September, during the dry season, a result similar to that observed in similar studies carried out in the same region [23,26,36]. The results also showed that the land use most susceptible to fire was the lowland dense ombrophilous forest, a result similar to that found by [23].…”
Section: Forest Fires and Anthropic Advance In The Western Amazonsupporting
confidence: 88%
See 1 more Smart Citation
“…The fire foci found in Rio Branco were concentrated in September, during the dry season, a result similar to that observed in similar studies carried out in the same region [23,26,36]. The results also showed that the land use most susceptible to fire was the lowland dense ombrophilous forest, a result similar to that found by [23].…”
Section: Forest Fires and Anthropic Advance In The Western Amazonsupporting
confidence: 88%
“…The kernel density is a methodology that provides greater reliability for analyzing fire behavior, as it transforms fire foci (points) into surface data [38]. In this aspect, our results showed a higher concentration of fire foci in Rio Branco during the dry season, following the pattern found by other studies [23,36,37].…”
Section: Forest Fires and Anthropic Advance In The Western Amazonsupporting
confidence: 86%
“…In Acre in the extreme southwest of the Brazilian Amazon, forest fires have already affected more than 500,000 ha of forests over the last 30 years, causing significant socioeconomic and environmental damage, including impacting tree species used by humans [18][19][20][21]. The increase in forest fires compromises Amazonian biodiversity, including species with high value to humans for timber and non-timber forest products, because few forest species are able to tolerate thermal stress, with most being poorly adapted to burning events [4].…”
Section: Introductionmentioning
confidence: 99%
“…The forest fire spread hazard refers to the possibility of a forest fire spreading (assuming that a forest fire has already begun) [1][2][3][4][5][6]. Under the influence of climate change and land use changes, the occurrence probability and intensity of extreme fires have increased significantly [7][8][9][10][11][12][13]. Under the combined action of flammable vegetation types, special dangerous terrains, and harsh meteorological conditions, the probability of forest fires spreading rapidly and out of control has increased significantly, seriously threatening forest resources and the habitats of wild animals and plants, as well as life and property security and homeland ecological security [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%